Metal artefact reduction in MRI at both 1.5 and 3.0 T using slice encoding for metal artefact correction and view angle tilting - Reichert, Miriam; Attenberger, Ulrike (British journal of radiology, 2015)
Objective: To compare metal artefact reduction in MRI at both 3.0 T and 1.5 T using different sequence strategies. Methods: Metal implants of stainless steel screw and plate within agarose phantoms and tissue specimens as well as three patients with implants were imaged at both 1.5 T and 3.0 T, using view angle tilting (VAT), slice encoding for metal artefact correction with VAT (SEMAC-VAT) and conventional sequence. Artefact reduction in agarose phantoms was quantitatively assessed by artefact volume measurements. Blinded reads were conducted in tissue specimen and human imaging, with respect to artefact size, distortion, blurring and overall image quality. Wilcoxon and Friedman tests for multiple comparisons and intraclass correlation coefficient (ICC) for interobserver agreement were performed with a significant level of p < 0.05. Results: Compared with conventional sequences, SEMAC-VAT significantly reduced metal artefacts by 83% ± 9% for the screw and 89% ± 3% for the plate at 1.5 T; 72% ± 7% for the screw and 38% ± 13% for the plate at 3.0 T (p < 0.05). In qualitative analysis, SEMAC-VAT allowed for better visualization of tissue structures adjacent to the implants and produced better overall image quality with good interobserver agreement for both tissue specimen and human imaging (ICC = 0.80-0.99; p < 0.001). In addition, VAT also markedly reduced metal artefacts compared with conventional sequence, but was inferior to SEMAC-VAT. Conclusion: SEMAC-VAT and VAT techniques effectively reduce artefacts from metal implants relative to conventional imaging at both 1.5 T and 3.0 T. Advances in knowledge: The feasibility of metal artefact reduction with SEMAC-VAT was demonstrated at 3.0-T MR. SEMAC-VAT significantly reduced metal artefacts at both 1.5 and 3.0 T. SEMAC-VAT allowed for better visualization of the tissue structures adjacent to the metal implants. SEMAC-VAT produced consistently better image quality in both tissue specimen and human imaging.